Dental and maxillomandibular incidental findings in panoramic radiography among individuals with mucopolysaccharidosis: a cross-sectional study - Natália Cristina Ruy CARNEIRO; Lucas Guimarães ABREU; Roselaine Moreira Coelho MILAGRES; Tania Mara Pimenta AMARAL; Carlos FLORES-MIR; Isabela Almeida PORDEUS; Ana Cristina BORGES-OLIVEIRA (University of São Paulo, 2021)
Abstract Mucopolysaccharidosis (MPS) is a group of rare and inherited metabolic disorders caused by the accumulation of macromolecule glycosaminoglycans inside lysosomes. Affected individuals may have dental and craniofacial tissue alterations, facilitating the development of several oral diseases. Objectives To assess, with panoramic radiographic images, the frequency of dental and maxillomandibular incidental findings among MPS individuals and compare them with non-MPS individuals. Methodology A cross-sectional study evaluating a sample of 14 MPS individuals and 28 non-MPS individuals aged from 5 to 26 years was carried out. They were matched for sex and age on a 2:1 proportion. Panoramic radiographs were assessed for the presence/absence of the following dental and maxillomandibular alterations: dental anomalies of number (hypodontia/dental agenesis, supernumerary teeth); anomalies of form (microdontia, macrodontia, conoid teeth, taurodontism, and root dilaceration); anomalies of position (impacted tooth, inverted tooth, tooth migration, partially bony teeth, complete bony teeth); periapical alterations (furcation lesion, circumscribed bone rarefaction); other alterations (radiolucent bone lesions, radiopaque bone lesions, radiopacity in the maxillary sinus, condylar hypoplasia). Differences between groups were tested by the Fisher's exact test and chi-square test (p<0.05). Results For intrarater agreement, Kappa values were 0.76 to 0.85. The presence of supernumerary teeth (p=0.003); conoid teeth (p=0.009); taurodontism (p<0.001); impacted teeth (p<0.001); partial bony teeth (p=0.040); complete bony teeth (p=0.013); and root dilaceration (p=0.047) were statistically more frequent in MPS individuals compared to non-MPS individuals. Bone rarefaction/furcation lesions (p=0.032), condylar hypoplasia (p<0.001), radiolucent bone lesions (p=0.001), and dentigerous cysts (p=0.002) were also more frequent in MPS individuals. Conclusion The presence of specific oral manifestations is more common in MPS individuals than non-MPS individuals.